Foliar abscisic acid (aba) concentration and leaf gas exchange properties of jatropha curcas subjected to water stress - Kamarul ain, Mustafa (2012)
hoetn000nal 411.4utopha nova. as a drought toletam Panthroning crop. mumble for Narneuth produrtion. bat groom ligalfiCONtly In /atilt non the thlegine management f manroM plotted uarate, tn ono of possak wank 4101ilW apart% raptors actuate utformation on water mu and Onwpfirsical prodanon chantrarritmer oral to aka Awing pl.mang gonna! Curren* there It no Ammiodge on gar tip 4 water rogatxs staatde far the antral. growth and dreb Polformanow of J rw paruadarly in Samoa block Jeans to be rrcMing rom,Nll all ?AM round MM.. alma.- and (ARAI conceafonatt and leaf ga emamagepapetnes 4 Jarropha arra abjecmi to won arms wive manual color ARA etwerotraton of J. coma, wrens& to a fold while to loaf manual COIldallaMe et) out redocod bn 3) the tall barn porennal t1ot tonat Gab field apono soave than I hIPa lathoosubeitc mkt IA: of plena grown *Ala annolcondnattru were OM:. with moot natal ranging Ma 13.69 to 103' bona Et' compared to than toxin YaitY,Elat It oh noun yahoo tonging ,front A39 to /347 :owl or' a' Amor ?who a mkt were hone... /edam, In •It JO 39 %front April to July after as the sal wave potential &woad from field copal:. to a 15 ldPa larbconag that water $111,1 &premed phatothruhmk capxim of A ratan A strung folaiouttlop between .1 and IA rogardles1 of Promunts et: - 0 86) was axonal ea/awing Mil phota”nawat was clack .stand to Me change, In the OW SSOLV141 conducathe and metal) plant growth perfialmanne was dant carne4itoi ter pnotoontaeac rates !Ode, blare HMI. thefOnfa6/ ' • •max of faint. ANA amoral plant in admoarion w &musk Arlen through oaoant otroore Aso redthartg ClIC(3.1•Ne trampetanat 11w rombumnra• of plostolognal wahanian that effector& potpie thr...ltanon and oloonar damage enable this motion to sonny AM hank ...onworn: mutt wywodartathe pc aipiralioN